Isolation of Antibiotic-Resistant Bacteria from the Toilet Door Handles in INTI International University - Kong, Melissa Suk Yi (2016)
The inanimate surfaces are reservoirs of various bacteria. Many bacteria can survive for weeks and months on the surfaces. One of the common surfaces that contain bacteria and can cause the transmission is the toilet door handle. Individuals that do not wash their hands after using the toilet touch the door handles and leads to the possible transmission of common bacteria, pathogens as well as antibiotic resistant bacteria from the toilet cubicles’ door handles of the female toilet at the academic block in INTI International University. All samples were inoculated on nutrient agar plate and incubated at 37 ˚C for 24 hours in a shaking incubator. All isolates were sub cultured and identified by a series tests such as Gram staining, catalase test, oxidase test and IMVIC test. These isolates were also grown on MSA and MacConkey Agar. A total of 56 pure isolates were isolated from the toilet door handles samples. Eight pure isolates showed Gram-negative reaction while 48 pure isolates showed Gram-positive reaction. Based on the Bergey’s Manual 9th edition, the possible bacterial species of Pseudomonas spp. (8.93%), Staphylococcus epidemidis (21.43%) and Staphylococcus aureus (26.79%) were isolated from the toilet door handles. There were 24 isolates (42.86%) that could not be identified due to lock of confirmatory tests. The antibiotic susceptibility test for the isolates were carried out using the Disk Diffusion Method on Muller-Hinton agar and the zone of inhibition were compared to BSAC guidelines, version 12 May 2013. From the 36 Gram-positive isolates, six isolates (16.67%) were resistant only to oxacillin and five of the isolates (13.89%) were only resistant to clindamycin. The antibiotic resistance of Gram-negative isolates could not be determined due to lack of information in the BSAC guidelines. A total of 11 out of 56 isolates (19.64%) were resistant to antibiotics. Hence, the chance of transmission of antibiotic resistance bacteria from the toilet door handles is relatively low and unlikely to cause a bacterial disease outbreak among the individual at INTI International University.